ISTILAH WARNA DALAM BAHASA INGGRIS & BAHASA MONGONDOW (SUATU ANALISIS KONTRASTIF) - BELENEHU, MOHAMMAD RIZKY; LASUT, THERESIA M.C.; RAMBING, ROSALINA R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research entitled â€œColor Terms in English and Mongondow Language :Â A Contrastive Analysisâ€Â isÂ an attempt to contrast color terms in both of the languages in terms of meaning, and symbol in order to find out the similarities and differences between English and Mongondow language. In terms of methodology, the writer uses descriptive method and contrastive analysis. The data on color terms were obtained by conducting library research related to color terms. The color termÂ in English language were obtained through several linguistic books and from several articles about color on internet. The data of Mongondow language collected by interviewing some informants. The data of both languages are analyzed based onÂ theories of Berlin & Kay, Wardhaugh, and Lado. The resuslt of this research shows that English and Mongondow language have similarities and differences. The similiarities are both of languages have basic color terms, they are black, white, red, yellow, green and brown. Both languages have the same meaning and symbol but are limited to certain colors. The differences are English has many color terms (basic color, color combination and color variation), while Mongondow language has only basic color.Â Keywords : Color terms, meaning, symbol, contrastive